Terms Educators in The Qoran - Ibrahim Hasan (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
This study aims to determine the terms educators contained in the Qoran. The results of this study is expected to add new perspectives and knowledge insights about educators contained in the Koran. This type of research includes library research, with using the thematic method (mauḍū'ī), which is to collect verses from the Qoran about educator terms. The approach used in this research is the science of tafsir, which is trying to see the term educator in the Koran which is interpreted by commentator. While the data collection technique uses the documentation technique from primary data sources in the form of Qoranic verses, plus secondary data sources in the form of tafsir books, and other supporting books related to with the object of research. The collected research data is then analyzed using the content analysis method through several methods step that is; maudhu’i (verse on the term educator), tahlili (verse analysis), muqaran (comparing the meaning of verse), and interpretation (make conclusion meaning of the verse). The results of this study indicate that there are terms educators in the Koran, namely: Murabbi, Mu'allim, Mudarris, Muzakki, Mursyid, Mudabbir, Mutli, Muwa’izd and Da'i.